War, humanitarian crises, population displacement, and fertility a review of evidence - Hill, Kenneth; ProQuest (Firm) (Washington DC : National Academies Press, 2004)
Includes statistical data.
Includes bibliograpical references, p. 26-28.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Demography; Fertility, Human; Disasters; Refugees; Electronic books